Authentic leadership and psychological well-being at the workplace : exploring the mediating role of perceived job security - Bannay, Dheyaa Falih; Hadi, Mohammed Jabbar (Penerbit Universiti Kebangsaan Malaysia, 2021)
The study of political economy after the concatenation of Iraq's post-war nation-state and the neoliberal conjuncture of 1990–2014 is challenging. The Gross Domestic Product (GDP) in Iraq has fluctuated dramatically over the past ten years, with all sectors being affected. Since authentic leadership and job security are essential organizational variables, more studies about critical variables such as psychological well-being at the workplace are to be expected. A challenging work environment and long working hours have led to increased psychological health requirements in the modern workplace. We aim to understand how well broad variables of leadership and perceived job security are correlated with nurses’ psychological well-being. The data were collected from 250 nurses. The indirect effects were examined with the Hayes process model. According to the findings of the study, authentic leadership has an impact on the psychological well-being of nurses. Moreover, the mediator variable (perceived job security) affects psychological well-being. The results of this study support the claim and substantiate the concept of authentic leadership in healthcare, which enables nurses to have more job security and consequently improves their psychological well-being. Leaders must demonstrate authentic leadership by being confident, optimistic, hopeful, and adaptable.